1990
DOI: 10.1002/ab.2480160603
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the evil empire: Horseplay and aggression

Abstract: The dominant mode of studying the antecedents of human aggression in psychology has been to look for these precursors in negative life events, for example, being physically punished, observing models using aggressive means, or experiencing forms of privation or frustration. In contrast, within the ethological literature, certain playful activities, in particular “play fighting,” have been interpreted as crucial precursors of later social activities, both aggressive and nonaggressive. Among humans, horseplay, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 47 publications
(16 reference statements)
7
28
0
Order By: Relevance
“…In contrast to this, however, a study of American college students found the incidence of young women actually kicking or punching males was relatively high and similar at 23% and 27%, respectively. However, in line with this study, females were also found to use a wide range of aggressive acts against males [Gergen 1990].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In contrast to this, however, a study of American college students found the incidence of young women actually kicking or punching males was relatively high and similar at 23% and 27%, respectively. However, in line with this study, females were also found to use a wide range of aggressive acts against males [Gergen 1990].…”
Section: Discussionsupporting
confidence: 68%
“…Thus, studies of dating relationships, as well as married/cohabiting relationships, have invariably found both incidences of men reporting victimization and women reporting perpetration at levels at or above the reverse case [for discussion and references see Carrado et al, 1996 andMorse, 1995]. It is also suggested that social norms, such as chivalry for male behavior, make it socially unacceptable for males to aggress toward a female [Gergen, 1990;Steinmetz, 1977] and that males in committed relationships may recognize the damage they may do to a relationship by assaulting their partner [Archer and Ray, 1989]. However, the slap the cad scenario that has been discussed in relation to the prevalence of female to male assaults in intimate relationships [Straus, 1993] may have been operative in the incidences of the victimization of male intimates and male strangers or social acquaintances.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although most aggression scales ask about aggression in general, some have specified whether the target is a same-sex other or a member of the opposite sex [Gergen, 1990;Harris, 1992;Hilton et al, 2000;Richardson and Green, 1999]. When such specifications have been made, the findings for sex differences in physical aggression show a marked contrast.…”
Section: Introductionmentioning
confidence: 88%
“…The frequency scale consisted of 25 aggressive actions that were taken from three sources all describing act-based measures of aggression [Gergen, 1990;Harris, 1992;Richardson and Green, 1999]. There are four dimensions, same-sex and partner direct and indirect aggression (Appendix A).…”
Section: Methodsmentioning
confidence: 99%